2022
DOI: 10.3390/nu14050966
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Advanced Glycation End Products on Female Reproduction: Review of Potential Mechanistic Pathways

Abstract: Advanced glycation end products (AGEs), a heterogenous group of products formed by the reaction between protein and reducing sugars, can form endogenously due to non-enzymatic reactions or by exogenous sources such as diet where considerable increase in AGEs is observed due to the modification of food mainly by thermal processing. Recent studies have suggested that AGEs could impact, via inducing inflammation and oxidative stress, the reproductive health and fertility in both males and females. This review pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 86 publications
0
3
0
3
Order By: Relevance
“…OS damage induced by AGEs may also induce inflammation and hypoxia, damaging the blood vessels of the ovaries and further accelerating ovarian aging [ 116 ]. In addition, AGEs can directly stimulate the production of extracellular matrix (ECM) and the abnormal cross-linking of collagen and elastin in the ovary, thus affecting the proliferation and division of granulosa cells and ultimately disrupting ovarian function [ 117 ].…”
Section: Factors Related To Os That Lead To Ovarian Agingmentioning
confidence: 99%
“…OS damage induced by AGEs may also induce inflammation and hypoxia, damaging the blood vessels of the ovaries and further accelerating ovarian aging [ 116 ]. In addition, AGEs can directly stimulate the production of extracellular matrix (ECM) and the abnormal cross-linking of collagen and elastin in the ovary, thus affecting the proliferation and division of granulosa cells and ultimately disrupting ovarian function [ 117 ].…”
Section: Factors Related To Os That Lead To Ovarian Agingmentioning
confidence: 99%
“…Indeed, overexpression of the AGE/RAGE is associated with COVID-19 severity and mortality [ 57 ]. Different studies confirmed that the overexpression of AGE/RAGE is correlated with the induction of the release of GDF15 ( Figure 2 ) [ 58 , 59 ].…”
Section: Growth Differentiation Factor 15 and Inflammatory Pathways I...mentioning
confidence: 68%
“…Besinlerle alınan AGE'ler esas olarak böbrekler tarafından temizlenir, yaklaşık üçte biri idrarla atılırken yaklaşık %50'si, tüketiminden birkaç gün sonra idrarda kalır ve vücutta birikir. Bu biriken AGE vücutta iltihaplanmaya ve oksidatif strese yol açar14 . Yüksek AGE içeren besinlerin tüketiminin hem sağlıklı bireylerde hem de kronik hastalığı olan hastalarda oksidatif stres, inflamasyon ve kardiyovasküler riskler ile ilişkili olduğu belirtilmiştir15 .…”
unclassified
“…Özellikle AGE ürünleri yumurtalık granüloza hücreleri üzerinde, hücre çoğalması ve hormon salınımı üzerinde toksik etki gösterir. Polikistik over sendromunda AGE'lerin rolü göz önüne alındığında besinlerle AGE alımının azaltılması önem taşımaktadır14 . İleri glikasyon son ürünleri, besinlerde doğal olarak bulunur ve besinlerin işlenmesi, sterilizasyonu, paketlenmesi ve uzun süreli depolanması dahil olmak üzere ısıyla ilgili ciddi endüstriyel prosedürler sırasında oluşumları artar31 .…”
unclassified
See 1 more Smart Citation